1986
DOI: 10.1182/blood.v68.3.652.652
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 3q21 abnormalities associated with hyperactive thrombopoiesis in acute blastic transformation of chronic myeloid leukemia

Abstract: Two patients with acute blastic transformation of chronic myeloid leukemia (CML) associated with strikingly elevated platelet counts showed abnormalities of chromosome 3q in addition to the standard Philadelphia (Ph1) chromosome translocation. The first patient had an inversion of chromosome 3 (q21q26) cytologically identical to an inversion 3 previously reported in de novo acute megakaryoblastic leukemia, and the second patient showed a translocation between chromosome 3q and the chromosome 9 homologue not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The Ph' Chromosome in CGL and Acute to the one reported in some patients with acute megakaryoblastic leukemia [32]. Rubin et al [33] recently sug-Lymphocytic Leukemia gested that a t(3:21)(q26;q22) is associated with myeloid BC and possibly fibrosis.…”
Section: Cytogenetic Pattern-aa or Anmentioning
confidence: 97%
“…The Ph' Chromosome in CGL and Acute to the one reported in some patients with acute megakaryoblastic leukemia [32]. Rubin et al [33] recently sug-Lymphocytic Leukemia gested that a t(3:21)(q26;q22) is associated with myeloid BC and possibly fibrosis.…”
Section: Cytogenetic Pattern-aa or Anmentioning
confidence: 97%
“…Leukaemia cell lines with specific chromosomal translocation have played important roles in the investigation of oncogenes involved in leukaemogenesis (Drexler, 1994;Drexler et al, 1995). The ectopic virus integration (EVI1) gene, which is located at chromosome band 3q26, is activated in the blast cells from patients with acute myelogenous leukaemia (AML) and chronic myelogenous leukaemia (CML) in blast crisis containing an inv(3)(q21q26) or a t(3;3)(q21;q26) (Bitter et al, 1985;Bernstein et al, 1986;Fonatsch et al, 1994). The EVI1 gene was originally identified as a gene associated with a common site of retroviral integration in murine myeloid leukaemias.…”
mentioning
confidence: 99%
“…Bernstein reported that cases with chromosome 3q abnormalities, such as our case, could easily convert to megakaryocytic feature in the acute phase [16]. However, chromosomal 3q abnormalities in blastic crisis are rare [17]. In our case, blasts did not become positive for CD4la until chromosome 3q abnormalities were appeared.…”
Section: Discussionmentioning
confidence: 46%